2018
DOI: 10.1111/ajr.12411
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis in the Kimberley region of Western Australia

Abstract: We found under-treatment and under-investigation of non-cystic fibrosis bronchiectasis in the Kimberley region. Five-year mortality was high, consistent with other rural Australian Indigenous cohorts. Following this audit, a strategy to improve awareness, as well as update and promote regional guidelines has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The study was conducted between October 2017 and June 2018 in two primary healthcare AMS (town and remote community) and a regional hospital in the Kimberley, Western Australia, known to have a high incidence of respiratory morbidity . The Kimberley is a vast and remote region with a tropical, monsoonal climate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was conducted between October 2017 and June 2018 in two primary healthcare AMS (town and remote community) and a regional hospital in the Kimberley, Western Australia, known to have a high incidence of respiratory morbidity . The Kimberley is a vast and remote region with a tropical, monsoonal climate.…”
Section: Methodsmentioning
confidence: 99%
“…6 Over time, PBB can lead to chronic suppurative lung disease (CSLD) and bronchiectasis, 2,7 which can occur in early childhood. 1 Bronchiectasis is prevalent in Aboriginal Australians and results in impaired general health, 8,9 reduced quality of life 10 and premature mortality, 11,12 contributing to the substantial gap in health outcomes and life expectancy between Aboriginal and non-Aboriginal people. 11,12 Children with PBB are typically preschool aged and apart from having a cough, appear well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In the Kimberley region of Australia, the median age at death for Aboriginal adults hospitalised with bronchiectasis is 33 years. 3 Early recognition leading to the diagnosis and treatment of the precursors of bronchiectasis, that is, protracted bacterial bronchitis (PBB) and chronic suppurative lung disease, can potentially prevent progression to irreversible bronchiectasis. [4][5][6] As chronic wet/productive cough is the dominant symptom of PBB and bronchiectasis 7 in children, recognition of this symptom by parents and health practitioners is necessary for early detection.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…A recent study reported that the average age of death in patients with bronchiectasis was 22 years younger in Aboriginal patients than non‐Aboriginal patients . In the Kimberley region of Australia, the median age at death for Aboriginal adults hospitalised with bronchiectasis is 33 years …”
mentioning
confidence: 99%